Response by gender of HIV-1-infected subjects treated with abacavir/lamivudine plus atazanavir, with or without ritonavir, for 144 weeks - Squires KE (Dove Medical Press, 2017)
Kathleen E Squires,1 Benjamin Young,2,3 Lizette Santiago,4 Robin H Dretler,5 Sharon L Walmsley,6 Henry H Zhao,7 Gary E Pakes,8 Lisa L Ross,8 Mark S Shaefer8 On behalf of the ARIES Study Team 1Thomas Jefferson University, Philadelphia, PA, 2Apex Family Medicine and Research, Denver, CO, 3International Association of Physicians in AIDS Care, Washington DC, USA; 4HOPE Clinic and Wellness Center, San Juan, Puerto Rico; 5ID Specialists of Atlanta, Decatur, GA, USA; 6University Health Network, Toronto, ON, Canada; 7GlaxoSmithKline, 8ViiV Healthcare, Research Triangle Park, NC, USA Purpose: The 144-week results of the open-label, multicenter Atazanavir/Ritonavir Induction with Epzicom Study (ARIES) were stratified by gender to compare treatment responses.Methods: A total of 369 HIV-infected, antiretroviral-naïve subjects receiving once-daily abacavir/lamivudine + atazanavir/ritonavir (ATV/r) whose HIV-1 RNA was <50 copies/mL by week 30 were randomized 1:1 at week 36 to maintain or discontinue ritonavir for 108 subsequent weeks. Between- and within-treatment gender-related efficacy and safety differences were analyzed.Results: Subjects were 85% male; 64% white; and had a mean age of 39 years, baseline median HIV-1 RNA of 114,815 copies/mL, and median CD4+ cell count of 198 cells/mm3. Gender (ATV [n=189]: 29 females/160 males; ATV/r [n=180]: 25 females/155 males) and most other demographics were similar between groups; more females than males were black (65% vs 25%) and fewer females had baseline HIV-1 RNA ≥100,000 copies/mL (41% vs 58%). At week 144, no significant differences between genders were observed in proportion maintaining HIV-1 RNA <50 copies/mL (ATV, 79% vs 77%; ATV/r, 60% vs 75%) or <400 copies/mL (ATV, 83% vs 84%; ATV/r, 68% vs 82%) (intent-to-treat-exposed: time to loss of virologic response analysis); median CD4+ change from baseline (ATV, +365 vs +300 cells/mm3; ATV/r, +344 vs +301 cells/mm3); proportion with treatment-related grade 2–4 adverse events (baseline to week 144: ATV, 41% vs 31%; ATV/r, 36% vs 43%; weeks 36 to 144: ATV, 14% vs 13%; ATV/r, 24% vs 23%); or proportion developing fasting lipid changes. Female and male virologic failure rates (ATV, 0 vs 5; ATV/r, 2 vs 4) and proportions completing the study were similar during the extension phase. Primary withdrawal reasons were loss to follow-up and pregnancy for females and loss to follow-up and other for males.Conclusion: Over 144 weeks, no significant gender differences were observed in efficacy, safety, or fasting lipid changes with abacavir/lamivudine +ATV or abacavir/lamivudine +ATV/r. Keywords: ARIES, HIV-infected, gender, virologic efficacy